Pollen-stigma interactions in Brassica oleracea. II. The fate of stigma surface proteins following pollination and their role in the self-incompatibility response. - Roberts, I; Harrod, G; Dickinson, H (1984)
Mature, self-incompatible stigmas exposed to cycloheximide for 2 h prior to pollination supported identical germination and growth of both cross and self pollen. Treatment of self-pollinated pistils with cycloheximide resulted in the germination of hitherto inactive pollen after some 2-4 h. Pollen germination and initial tube growth in an in vitro germination medium were not significantly affected by cycloheximide. A continuous synthesis of stigmatic proteins is therefore essential for the operation of the self-incompatibility (S.I.) system. However, light-microscope autoradiography of stigmas fed with L-[3H]leucine prior to pollination revealed no movement of stigmatic proteins into the pollen, independent of the compatibility of the pollen with respect to the stigma. Further, tunicamycin, when applied in the same way as cycloheximide, had no effect on the S.I. system. These results are discussed in terms of the proposed cycling of proteins in the papillar cell wall and the involvement of a stigmatic glycoprotein in the S.I. response.